Alterations in soil pH emerge as a key driver of the impact of global change on soil microbial nitrogen cycling: Evidence from a global meta‐analysis. Issue 1 (20th November 2022) - Zhong, Yangquanwei; Yan, Weiming; Canisares, Lucas P.; Wang, Shi; Brodie, Eoin L.
Abstract: Aim: Soil nitrogen (N) cycling is critical to the productivity of terrestrial ecosystems. However, the impact of global change factors (GCFs) on the microbial mediators of N cycling pathways has yet to be synthesized, and it also remains unclear whether the response of the abundance of N‐cycling genes can predict changes in their corresponding processes. Location: Global. Time period: 2000–2021. Major taxa studied: Archaea, bacteria. Methods: We synthesized 8322 paired observations of soil microorganisms related to N cycling from field experiments in which GCFs (climate change and nutrient addition) were manipulated. Results: We found that the abundance of soil microbes and most N‐cycling genes were resistant to elevated CO2, experimental warming and water addition/reduction; however, N addition and the combination of N addition with other GCFs significantly increased the abundance of ammonia oxidizer bacteria ( amoA‐AOB ). The results indicated that in steady‐state (natural) conditions, the main factors driving the global abundance of soil bacteria, archaea and N‐cycling genes varied in terms of the contributions of climatic and edaphic factors. However, upon manipulation of GCFs, the induced change in soil pH was the most essential factor associated with changes in the abundance of soil microbes and N‐cycling genes. Notably, the changes in ammonia‐oxidizing archaea ( amoA‐AOA ) and amoA‐AOB genes, in addition to genes involved in denitrification ( nirS and nirK ), were significantly correlated with the rates of their corresponding processes, but GCF‐induced shifts in the potential nitrification rate (PNR) were explained well by changes in the abundance of the amoA‐AOB gene under GCFs. Main conclusions: Our study highlights how ongoing GCFs impact the abundance of soil microbes and N‐cycling genes, which might have a profound impact on terrestrial N cycling. Our field‐based results provide new insights into the drivers of the abundance of soil microbes and N‐cycling genes.